Facile preparation of TPE/SiO2 flexible superhydrophobic composite film with acid corrosion resistance and stretchable recyclability. (December 2020) - Wang, Bo; Liu, Hongtao; Chen, Chao; Zhang, Huaqiu; Du, Chunchun; Zhou, Lizao
Highlights: A flexible superhydrophobic composite film was prepared by a simple solvent blending method. The composite film can maintain superhydrophobicity under different tensile strains with large WCAs and small WSAs. After cyclic stretching for 200 % at strain for 500 times, the composite film surface still has good hydrophobic property. The film has excellent acid corrosion resistance with increased superhydrophobic property even after 15 days of immersion. Abstract: Thermoplastic elastomers/silica (TPE/SiO2 ) flexible superhydrophobic composite film was prepared by solvent blending and (Heptadecafluoro-1, 1, 2, 2-tetradecyl) trimethoxysilane (FAS-17) modification. The obtained TPE/17.5 % SiO2 composite film has the best comprehensive performance, which can maintain superhydrophobicity under different tensile strains with large water contact angles of ＞ 151.0° and small sliding angles of ＜ 10.0°. After cyclic stretching for 200 % at strain for 500 times, the composite film surface still has good hydrophobic property. In addition, it has excellent acid corrosion resistance, the water contact angles of the composite film surface have no decrease but increase after immersion in hydrochloric acid solution. Even after 15 days of immersion corrosion, the surface remains superhydrophobic, which can be applied by means of film sticking for decoration, construction, automobile and electronics, etc.